Brain and platelet serotonin transporter in humans—correlation between [ 123I]-ADAM SPECT and serotonergic measurements in platelets - Uebelhack, Ralf; Franke, Leonora; Herold, Nathalie; Plotkin, Michael; Amthauer, Holger; Felix, Roland (Neuroscience letters, 2006)
Blood platelets are thought to be a useful peripheral model for investigating the central serotoninergic mechanisms associated with the serotonin transporter (SERT). On the other hand, an in vivo investigation of SERT in the human brain has been made possible by the development of several promising SPECT radioligands, such as [ 123I]-ADAM. The aim of the present study was to investigate the possible correlation between the SERT measurements in the brain and those in platelets. Forty-four subjects (14 healthy subjects and 30 patients with the diagnosis of major depression or schizoaffective disorder) were examined. The [ 123I]-ADAM binding was assessed 4 h after injection using MR-guided regions of interest (ROIs) in the midbrain and cerebellum. In a parallel investigation, serotonin (5HT) concentration and kinetic characteristics of 5HT uptake activity ( V max and K m) were determined in platelet-rich plasma. Overall, there was no significant correlation between the V max of 5HT uptake in platelets and the specific to nonspecific partition coefficient of [ 123I]-ADAM (V″ 3) in the midbrain. However, low but significant Pearson correlation coefficients were found for V max and normalised activities measured in the midbrain ( r = 0.310, p = 0.043). The correlation was stronger and significant in females ( n = 20, r = 0.629, p = 0.003) but low and non-significant in the 24 males ( r = 0.104). Although confirmation is necessary, it seems that the relationship between different indices of [ 123I]-ADAM binding in the brain and 5HT uptake characteristics in platelets is complex, nonuniform, and possibly gender-specific.